2012
DOI: 10.1038/onc.2012.502
|View full text |Cite
|
Sign up to set email alerts
|

WIP1 phosphatase modulates the Hedgehog signaling by enhancing GLI1 function

Abstract: The Hedgehog-GLI (HH-GLI) signaling plays a critical role in controlling growth and tissue patterning during embryogenesis and is implicated in a variety of human malignancies, including those of the skin. Phosphorylation events have been shown to regulate the activity of the GLI transcription factors, the final effectors of the HH-GLI signaling pathway. Here, we show that WIP1 (or PPM1D), an oncogenic phosphatase amplified/overexpressed in several types of human cancer, is a positive modulator of the HH signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 73 publications
0
53
0
Order By: Relevance
“…Specific knockdown of IPO7 expression using siRNA resulted in reduced nuclear accumulation of GLI1, indicating the dependence of nuclear import of GLI1 on IPO7. Previous studies demonstrated that several molecules may affect nuclear localization of GLI1 (22)(23)(24)(25). For example, nuclear entry of GLI1 was regulated by its nuclear import factor Imp␤1 (importin ␤1) and SuFu (22); WIP1 (or PPM1D) enhanced the function of GLI1 by increasing its nuclear localization (23); Rab23 reduced the (24); and SHP (small heterodimer partner) inhibited GLI1 nuclear localization (25).…”
Section: Discussionmentioning
confidence: 99%
“…Specific knockdown of IPO7 expression using siRNA resulted in reduced nuclear accumulation of GLI1, indicating the dependence of nuclear import of GLI1 on IPO7. Previous studies demonstrated that several molecules may affect nuclear localization of GLI1 (22)(23)(24)(25). For example, nuclear entry of GLI1 was regulated by its nuclear import factor Imp␤1 (importin ␤1) and SuFu (22); WIP1 (or PPM1D) enhanced the function of GLI1 by increasing its nuclear localization (23); Rab23 reduced the (24); and SHP (small heterodimer partner) inhibited GLI1 nuclear localization (25).…”
Section: Discussionmentioning
confidence: 99%
“…PPM1D may also contribute to malignancy and metastasis. In this regard, it has recently been demonstrated that PPM1D promotes the stabilization of Gli1, a transcription factor known to promote the expression of proteins involved in stemness and epithelial to mesenchymal transition (EMT) [59]. While the staining intensity of PPM1D in chemonaive tumors in this study did not predict PFS, it should be noted that the baseline levels of PPM1D in chemosensitive and chemoresistant cell lines are not different, and it is the differential response to CDDP that appears to be important.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted as previously described [59]. A2780cp cells were infected with adeno-DN-Akt (MOI ¼ 80; 24 h) or adeno-LacZ as a control, then incubated with leucine-deficient RPMI1640 media supplemented with dialyzed FBS (24 h).…”
Section: Pulse-chase Assaymentioning
confidence: 99%
“…The first hint comes from the identification of GLI-1 as a substrate of ITCH [109,110] and from the observation that ATM modulates ITCH [65]. A second hint comes from the observation that WIP1, a Ser/Thr phosphatase aberrantly upregulated in cancer that dephosphorylates and modulates, among other targets, also ATM activity [111], is involved in the modulation of the SHH signaling [112]. It has been proposed that during tumorigenesis WIP1 (wild-type p53-induced phosphatase 1) overexpression might contribute to increase proliferative and self-renewing activities of GLI-1, therefore enabling an expansion of cancer stem cells and derived progenitors that sustain tumor growth [112].…”
Section: Atm Dependent Modulation Of Signaling Pathways Outside Ddr Imentioning
confidence: 99%